PENGARUH CONSUMERS EXCITEMENT, CONSUMERS ESTEEM DAN IMPULSE BUYING INTENTION TERHADAP IMPULSE BUYING BEHAVIOR PADA KONSUMEN HYPERMART CIPUTRA WORLD SURABAYA - WIJOYO, DEVIANA (Universitas Katolik Widya Mandala Surabaya, 2013)
The purpose of this study was to determine the effect of excitement consumers, consumers esteem and impulse buying intention on impulse buying behavior. Design of this study was to use a causal hypothesis whereby causal research is research that aims to determine the relationship of a causal occurrence of a phenomenon of the factors that influence consumer impulse buying behavior in the food or beverage products are sold around the cashier Hypermart in Surabaya. The type of data in this research is quantitative data, the data used in this study is primary data is data obtained directly from the 130 respondents as a source of research. The study states that the impulse buying intention significantly effect on impulse buying behavior. Impulse buying intention mediate relations with antacedents impulse buying behavior, namely (a) the consumer excitement and (b) consumer esteem. The results also suggested that consumer excitement significant effect on impulse buying intention and impulse buying behavior. Consumer esteem whereas significant effect on impulse buying intention and impulse buying behavior.